The Woodrat Gut Microbiota as an Experimental System for Understanding Microbial Metabolism of Dietary Toxins - Kohl, Kevin D.; Dearing, M. Denise (Frontiers in Microbiology, 2016)
The microbial communities inhabiting the alimentary tracts of mammals, particularly those of herbivores, are estimated to be one of the densest microbial reservoirs on Earth. The significance of these gut microbes in influencing the physiology, ecology and evolution of their hosts is only beginning to be realized. To understand the microbiome of herbivores with a focus on nutritional ecology, while evaluating the roles of host evolution and environment in sculpting microbial diversity, we have developed an experimental system consisting of the microbial communities of several species of herbivorous woodrats (genus Neotoma) that naturally feed on a variety of dietary toxins. We designed this system to investigate the long-standing, but experimentally neglected hypothesis that ingestion of toxic diets by herbivores is facilitated by the gut microbiota. Like several other rodent species, the woodrat stomach has a sacculated, nongastric foregut portion. We have documented a dense and diverse community of microbes in the woodrat foregut, with several genera potentially capable of degrading dietary toxins and/or playing a role in stimulating hepatic detoxification enzymes of the host. The biodiversity of these gut microbes appears to be a function of host evolution, ecological experience and diet, such that dietary toxins increase microbial diversity in hosts with experience with these toxins while novel toxins depress microbial diversity. These microbial communities are critical to the ingestion of a toxic diet as reducing the microbial community with antibiotics impairs the host’s ability to feed on dietary toxins. Furthermore, the detoxification capacity of gut microbes can be transferred from Neotoma both intra and interspecifically to naïve animals that lack ecological and evolutionary history with these toxins. In addition to advancing our knowledge of complex host-microbes interactions, this system holds promise for identifying microbes that could be useful in the treatment of diseases in humans and domestic animals.